Parametric and Non Parametric Methods for Efficiency Assessment of State Higher Vocational Schools in 2009-2011 - Lesław Rządziński; Anna Sworowska (Entrepreneurial Business and Economics Review)
Objective: As a great number of higher schools in Poland are financed from public resources, there arises a question about the adequacy of those schools' inputs to the obtained outputs. The aim of this paper is to examine the technical efficiency of 27 state higher vocational schools in Poland.